2010
DOI: 10.1144/sp340.8
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous–Neogene tectonic evolution of the northern margin of the Black Sea from seismic reflection data and tectonic subsidence analysis

Abstract: Three fundamental stages of the Cretaceous–Neogene tectonic evolution of the Odessa Shelf and Azov Sea (northern margins of western and eastern Black Sea basins, respectively) have been documented from the analysis of reinterpreted regional seismic profiling and one-dimensional (1-D) subsidence analysis of 49 wells, for which the stratigraphic interpretation was recently revised. (1) An initial active rifting stage began within the Early Cretaceous (not later than Aptian–Albian times) and continued until the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 25 publications
7
41
0
2
Order By: Relevance
“…Wide open anticlines or smaller-scale folds formed along the same type of highangle reverse faults with reduced offsets activated earlier during the Oligocene -early Miocene [Afanasenkov et al, 2007;Khriachtchevskaia et al, 2010].…”
Section: Timing Of Inversionmentioning
confidence: 99%
“…Wide open anticlines or smaller-scale folds formed along the same type of highangle reverse faults with reduced offsets activated earlier during the Oligocene -early Miocene [Afanasenkov et al, 2007;Khriachtchevskaia et al, 2010].…”
Section: Timing Of Inversionmentioning
confidence: 99%
“…There is also good evidence of a compressional regime in this area in the Eocene (cf. Khriachtchevskaia et al 2010;Sheremet et al 2016a) in contiguous offshore regions, although they indicate that the most intense period of shortening began later. Significant volcanic activity also occurs in the Eocene in the study area, as reported by Sahakyan et al (2016) in the Lesser Caucasus and Hippolyte et al (2015) in the eastern Pontides.…”
Section: Synthesis and Summarymentioning
confidence: 99%
“…The onset of inversion tectonics is fairly precisely dated by structural relationships seen in seismic data on the northern margin of the Black Sea as late Middle Eocene (Khriachtchevskaia et al 2010), following a period of relative quiescence. However, extension following Late Cretaceous obduction processes on the SE margin of the TASA block in SE Turkey and on the Arabian Plate continued until the Middle Eocene possibly due to roll-back of the slab related to the southern Neotethys Oceanic .…”
Section: Inversion: Compression and Magmatismmentioning
confidence: 99%
“…The extensional events, including the formation of the Black Sea basin, that took place mainly during middle-Late Cretaceous times (Bergerat et al 2010;Kaymakci et al 2010;Khriachtchevskaia et al 2010;Konerding et al 2010) were replaced as subduction terminated in the northern Neotethys and collision of the intervening continental terranes began, leading to inversion tectonics throughout the circum-Black Sea area. The onset of inversion tectonics is fairly precisely dated by structural relationships seen in seismic data on the northern margin of the Black Sea as late Middle Eocene (Khriachtchevskaia et al 2010), following a period of relative quiescence.…”
Section: Inversion: Compression and Magmatismmentioning
confidence: 99%
See 1 more Smart Citation